Determinação voltamétrica multivariada simultânea de compostos fenólicos - Gomes , Gláucio Jefferson Araújo (2015)
Phenolic compounds hydroquinone, catechol, resorcinol and cresol have a wide industrial application and are currently present in the environment especially because of human activity. These compounds can pose a threat to various environmental systems, since they are difficult to degrade and exhibit high toxicity. This work aims to develop a method for simultaneous determination of these phenolic compounds, associating the electrochemical determination to multivariate analysis. For this, four types of electrodes were tested using differential pulse voltammetry, whose parameters were optimized by performing a complete 23 factorial design. Calibration set was obtained by performing a Brereton-type factorial design in five levels. Partial least squares (PLS) and multiple linear regression associated with selection of variables by the genetic algorithm (GA-MLR) or by the successive projections algorithm (SPA-MLR) were used as regression techniques. It was found that the carbon nanotubes paste electrode showed electrochemical response to HQ, CC, RS and CR at 0.2V, 0.3V, 0.75V and 0.65V, respectively. Models obtained by GA-MLR showed the best predictions of the concentrations of the studied analytes in the micromolar range.